(untitled) (Altre Modernità, 2020)
The present article aims to identify and analyze the representations of cultural identities in the literary texts of a study program in the area of Language and Communication. The context of study corresponds to the sixth basic level of the Chilean formal education system. The methodology is of interdisciplinary nature, combining linguistic and semiotic analysis. The main findings demonstrate that the study texts contain a scarce variety of representations of cultural identities, giving priority to the representations of Chilean national cultural identities, i.e. of mostly female authorship, and of authors age linked to the image of grandparents. Following this, the next group is the ‘universal’ representations of Western European culture, linked to the colonization processes, and to the detriment of representations of Latin American cultural identities. The absent representations correspond to the identities linked to the cultures of Asia, Oceania and Africa. Thus, the article highlights the need to consider representations of varied cultural identities, with an emphasis on Latin Americans, specially the cultures of migrant groups; as well as the consideration of contemporary representations of ethnic groups.